Seasonal influenza vaccination during a pandemic - Heather Richmond; Natasha Rees; Sharon McHale; Aaron Rak; Jonathan Anderson (Taylor & Francis Group, 2020)
In the Northern Hemisphere, the persistence or reemergence of coronavirus circulation into the 2020-2021 influenza season threatens to overwhelm health-care resources and systems and increase mortality and morbidity. Data from Australia show that stay-at-home policies have reduced both influenza and coronavirus cases early in the season, thus "flattening the curve." However, influenza vaccination is critical to ensure the reduction in co-infection. Several policies, such as vaccination strategies to accommodate physical distancing measures, change population recommendations, and timing and location of vaccination have been implemented to increase influenza vaccine uptake during the pandemic. This commentary explores those policies.